Literature Review of Extended Reality Research in Consumer Experience: Insight From Semantic Network Analysis and Topic Modeling - Choi, Hansol; Lee, Hyemi (Asia Marketing Journal (Online), 2024)
Extended Reality (XR) technology, the umbrella term covering hyper-realistic technologies, is known to enhance consumer experience and is therefore developing rapidly and being utilized across various industries. Growing studies have examined XR technology and consumer experience; however, the literature has failed to fully explore hyper-realistic technology through a holistic perspective. To fill this gap, we analyzed 720 Korean and international articles through semantic network analysis and topic modeling and identified the literature on XR research in consumer experience. As a result, we extracted six main topics: “Tourism,” “Buying Behavior,” “XR Technology Acceptance,” “Virtual Space,” “Game,” and “XR Environment.” The results provide comprehensive insight on XR technology in consumer experience, whereas the literature is bounded on the production side as revealing a lack of academic discourse on consumer rights and responsibilities. Research reflecting the consumer welfare perspective is, therefore, recommended for future studies.